The Holy and the Unholy in Chaucer’S Squire’S Tale - Czarnowus, Anna (Studia Anglica Posnaniensia, 2013)
As Richard Kieckhefer once noticed, “the holy” and “the unholy” were interlocking phenomena in the medieval culture. Such a perspective on religion and magic may, indeed, be seen in possible sources of Chaucer’s Squire’s tale, John Carpini’s Historia Mongalorum and in Historia Tartarorum, attributed either to Benedict the Pole, a member of the 1245 papal mission to Mongols, or to the scribe, “C. de Bridia”. Perhaps Carpini and Benedict projected their Christian perception of magic as connected with religion onto the Tartar world they experienced. The Mongol beliefs they related may have been the very convictions mentioned by Chaucer in the discussion of Cambuskyan’s “secte”. The tale then proceeds to a discussion of magic, but the magic there is no longer “unholy”, as opposed to “the holy”, but technological, manmade, and unnatural. The texts portray two stages in a medieval approach to magic, which were followed by the Renaissance condemnation of magic as heretical. In Squire’s tale magic leads to the experience of wonder, which unites the community.